Metric Goodness and Measurement Invariance of the Italian Brief Version of Interpersonal Reactivity Index: A Study With Young Adults - Diotaiuti, Pierluigi; Valente, Giuseppe; Mancone, Stefania; Grambone, Angela; Chirico, Andrea (Frontiers in Psychology, 2021)
The Interpersonal Reactivity Index (IRI) is a widely used multidimensional measure to assess empathy across four main dimensions: perspective taking (PT) empathic concern (EC) personal distress (PD) fantasy (F). This study concerns a new 16 items shortened version of the Interpersonal Reactivity Index that showed good fits with both the CFA (χ2 = 117.967; df = 91; CFI = .975; TLI = .968; RMSEA = .031) and the gender Measurement Invariance. A total of 683 Italian university students participated in a non-probabilistic sampling. The internal consistency measures were found to be fully satisfactory. Convergent validity was tested by the correlations with the Prosocialness Scale for Adults (PSA) and The Toronto Alexithymia Scale-20 (TAS-20). As hypothesized the measure proved good convergent validity with Prosocialness, i.e. the willingness to assist, help, share, care and empathy with others, and a relevant inverse association with the External Oriented Thinking (EOT), characterizing individuals with emotionally poor thinking. This research provided additional evidence for a link between alexithymia and poor empathic abilities. The instrument is therefore proposed for evaluative use in clinical and educational settings. IRI-B could be useful for its predictive value especially in adolescence as alexithymic components have been often associated with various forms of addiction, eating disorders, post-traumatic disorders, abuse and violence suffered. Considering the antecedent role that empathic dimensions have for altruistic activation, IRI-B could also find utilization to explore the personality correlates of caregivers who serve in helping settings (physicians, nurses, and volunteers), contributing to predict both their emotional availability to the suffering of others and potential signs of professional burnout.